Strategi Komunikasi Pemasaran Sekutu Kopi Surakarta dalam Meningkatkan Jumlah Konsumen Mellui Media Sosial Instagram @sekutukopi - Adinda Fauzia Armedina; Eka Nada Shofa Alkhajar (Universitas Sebelas Maret (UNS), 2025)
The AISAS (Attention, Interest, Search, Action, Share) model of consumption behavior has emerged as a relevant and contemporary marketing strategy. With its emphasis on flexibility and adaptability, the AISAS model aligns well with the digital era and the evolving habits of modern consumers. This study adopts a qualitative descriptive approach and utilizes the AISAS model as its theoretical framework. The research aims to explore the marketing communication strategies employed by Sekutu Kopi to attract and engage consumers. Data was collected through in-depth interviews with key informants, including the founder and co-founder of Sekutu Kopi, the creative team leader, social media specialist, and photographer/videographer. The findings were analyzed qualitatively, focusing on how the AISAS strategy was implemented by Sekutu Kopi. The study reveals that Instagram plays a significant role in influencing public perception and promoting products. Specifically, it highlights how Sekutu Kopi effectively leverages Instagram to increase brand visibility and consumer interest. The research also outlines which aspects of the strategy have already been implemented and identifies potential areas for further development.